0
$\begingroup$

N has probability mass function: $p_o = p_1 =0$ and $p_k = \frac{1}{(e^1-2)k!}$ for $k=2,3,4,...$ I Solved for the pgf of N and got $G(t) = \frac{e^t}{e^1-2}$

How do I calculate $E[N^2 | N>2]$?

$\endgroup$
4
  • $\begingroup$ $\sum\limits_{k=2}^\infty 1/(e^1k!) = 1-2e^{-1} \approx 0.26424$ so that would not be a probability mass function $\endgroup$
    – Henry
    Jul 21 '20 at 0:05
  • $\begingroup$ What I did was $\sum_{k=1}^{\infty} \frac{c}{k!} = 1$ which using exp series gave $ce^1=1$ Did I do anything wrong here? $\endgroup$ Jul 21 '20 at 0:11
  • $\begingroup$ You need to decide whether your sum starts with $0$ or $1$ or $2$ or $3$. Though it does not really matter if you are conditioning on $N \gt 2$ $\endgroup$
    – Henry
    Jul 21 '20 at 0:23
  • $\begingroup$ Did I get the pmf wrong? The c value I got was 1/e $\endgroup$ Jul 21 '20 at 0:28
1
$\begingroup$

\begin{align} \mathbb{E}[N^2 | N > 2] &= \sum_{n=0}^\infty n^2 Pr(N=n|N>2) \\ &= \frac1{1-P(N\le 2)}\sum_{n=3}^\infty n^2\cdot \frac{1}{(e-2)n!} \\ &=\frac1{1-\frac1{2(e-2)}}\sum_{n=3}^\infty n\cdot \frac{1}{(e-2)(n-1)!} \\ &= \frac1{1-\frac1{2(e-2)}}\sum_{n=3}^\infty (n-1+1)\cdot \frac{1}{(e-2)(n-1)!} \\ &=\frac{2}{2(e-2)-1} \left(\sum_{n=3}^\infty \frac{1}{(n-2)!} + \sum_{n=3}^\infty \frac{1}{(n-1)!} \right) \end{align}

I am leaving the last step for you to simplify.

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.